1976
DOI: 10.1161/01.str.7.4.416
|View full text |Cite
|
Sign up to set email alerts
|

Carotid blood velocity during cough studies in man.

Abstract: SUMMARY Utilizing a Doppler ultrasonic flownteter catheter, right carotid artery blood velocity was measured during 91 coughing episodes in 16 patients. Such coughing reduced carotid blood velocity by 40 ± 22% (control = 34 ± 8 cm per second, cough = 20 ± 9 cm per second, p < 0.001). There was an insignificant low degree of correlation between the level of simultaneously recorded mean right pressure and the percent decline of peak carotid blood velocity, suggesting that impaired venous return was not the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In addition to measuring volume changes during coughing we were also able to calculate blood shift out of the trunk. Coughing is known to be associated with reductions in carotid artery (Desser et al 1976) and cerebral blood flow (Mattle et al 1995; Chao et al 2007), hypotension and bradycardia (Benditt et al 2005; Chao et al 2007), and on occasion can result in syncope. Whilst this study cannot shed light on the underlying mechanisms in cough syncope, it does suggest that during a peal of voluntary coughing significant haemodynamic shifts occur.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to measuring volume changes during coughing we were also able to calculate blood shift out of the trunk. Coughing is known to be associated with reductions in carotid artery (Desser et al 1976) and cerebral blood flow (Mattle et al 1995; Chao et al 2007), hypotension and bradycardia (Benditt et al 2005; Chao et al 2007), and on occasion can result in syncope. Whilst this study cannot shed light on the underlying mechanisms in cough syncope, it does suggest that during a peal of voluntary coughing significant haemodynamic shifts occur.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rise in intrathoracic pressure is associated with a rise in intracranial pressure [1]. Moreover, it has been confirmed that coughing diminishes phasic carotid blood velocity and reduces cerebral perfusion [16]. In the past, “inability to sneeze” was observed after cerebral lesions [4, 5] and a variety of neurological disorders (other than syncope) were reported after sneezing; they included vertigo and deafness, subarachnoid haemorrhage and headache, drop attacks (in cases of Arnold-Chiari malformation), cerebrospinal fluid rhinorrhoea and pneumocephalus, or sudden quadriplegia after acute cervical disc herniation [1, 17].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that short bursts of coughing can decrease the velocity of arterial flow (in the carotid and middle cerebral arteries) (Desser et al 1976;Chao et al 2007). Desser et al (1976) suggested that increased intracranial pressure caused by an influx of CSF may act to impede arterial flow into the cranium, as the velocity in the carotid artery was reduced by the cough but the velocity in the aorta was unaffected. This mechanism may explain the decreased arterial flow measured in this study ( Fig.…”
Section: The Influence Of Arterial Flow During Short Respiratory Manomentioning
confidence: 99%